STUDI ETNOBOTANI TUMBUHAN PANGAN YANG TIDAK DIBUDIDAYAKAN OLEH MASYARAKAT LOKAL SUB-ETNIS BATAK TOBA, DI DESA PEADUNGDUNG SUMATERA UTARA, INDONESIA - Marina Silalahi; Nisyawati Nisyawati; Ria Anggraeni (Graduate School Bogor Agricultural University (SPs IPB), 2018)
The Batak Toba sub-ethnic is an indegenous tribe in Sumatra Island, who has local knowledge of using plants as food (edible plants). This study aims to (1) document the non-cultivated plants used by Batak Toba sub-ethnic as edible plants; (2) compare the quantitative values of edible plants by Batak Toba sub-ethnic. The study was conducted with ethnobotany approach through surveys and parcifative observations. The interviews were conducted toward key informants (7 people) and the general respondents (30 people). The general respondents were grouped into 17-30 years old, 30-50 years old, more than 50 years old, which the numbers of each were 10 respondents. The data were analyzed qualitatively and quantitatively. The quantitative analysis was done by calculating the relative frequency of citation (RFC), and informant consensus factor (ICF). This research found a total of 44 species belonging to the 28 families and 40 genera have been used by Batak Toba sub-ethnic as edible plants. The edible plants have been used as vegetables (18 species), fruits (16 species), spices (6 species), and drinks (3 species). The mean of species known by respondents were 15.8 ± 5.18 (17-30 years old), 23.2 ± 3.58 (30-50 years old), 26.8 ± 4.66 (> 50 years old) and 36.85 ± 5.11 (key informants). The IFC values of edible plants were 0.943 (spices) - 0.968 (drinks). A total of nine species of foodstuffs have been known by all respondents (RFC = 1.0). The utilization of Calamus javensis and Arundina graminifolia, as foodstuffs are going to be further investigated as low-calorie of carbohydrate sources.